Half of all peripheral intravenous lines in an Australian tertiary emergency department are unused: Pain with no gain? - Limm, E.; Fang, X.; Dendle, C.; Stuart, R.; Egerton-Warburton, Diana (Mosby, 2013)
Study objective: Our study aims to determine the incidence of unused peripheral intravenous cannulas inserted in the emergency department (ED). Methods: A retrospective cohort study using a structured electronic medical record review was performed in a 640-bed tertiary care hospital in Melbourne, Australia. During a 30-day period, all patients who had a peripheral intravenous cannula recorded as a procedure on their electronic medical record in the ED were included in this study. Results: Fifty percent of peripheral intravenous cannulas inserted in the ED were unused. Patients presenting with obstetric and gynecologic and neurologic symptoms were significantly more likely to have an unused cannula. Forty-three percent of patients admitted to the hospital with unused peripheral intravenous cannulas in the ED continued to have them unused 72 hours later. Conclusion: There is a high incidence of unused peripheral intravenous cannulas inserted in the ED. The risk of having an unused peripheral intravenous cannula is associated with the patient's presenting complaint. Efforts should be directed to reduce this rate of unused peripheral intravenous cannula insertion, especially in patients being admitted, to minimize the risk of complications.